Cuantificación del rendimiento y productividad en elementos estructurales de concreto reforzado en edificios modulares en altura - Montero-Moreira, Juan Pablo (Instituto Tecnológico de Costa Rica, 2010)
Construction, like all other industries, is in a constant search of improvement. Yet, despite the advances in technological tools and materials, its principle asset remains to be its human resource. The principle objective of this project was the elaboration of a data bank for the construction company “Hogares de Costa Rica S.A.” which intends to utilize the tool for project programming and cost estimation while keeping in mind the productivity and performance of it workers in the construction of tall buildings built with reinforced concrete. This project was carried out in the Condominium 6-30, an apartment complex of more than 24,000 m² of construction, including two towers that will house a combined total 200 units. In construction of Tower A, a new process was utilized that permits the creation of monolithic structures based on the use of Forsa concrete forms. While carrying out the project, expected trends were identified for construction processes including proper placement of steel reinforcement, proper placement of concrete, and the removal of concrete forms, which will serve as a basis for projects like Tower B.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción). Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2010.
Keywords: Muestreo; Rendimiento; Acero; Productividad; Mano de obra